2021
DOI: 10.1002/ange.202014037
|View full text |Cite
|
Sign up to set email alerts
|

Site Sensitivity of Interfacial Charge Transfer and Photocatalytic Efficiency in Photocatalysis: Methanol Oxidation on Anatase TiO2 Nanocrystals

Abstract: Photocatalytic oxidation of methanol on various anatase TiO2 nanocrystals was studied by in situ and time‐resolved characterizations and DFT calculations. Surface site and resulting surface adsorbates affect the surface band bending/bulk‐to‐surface charge migration processes and interfacial electronic structure/interfacial charge transfer processes. TiO2 nanocrystals predominantly enclosed by the {001} facets expose a high density of reactive fourfold‐coordinated Ti sites (Ti4c) at which CH3OH molecules dissoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Since the discovery that TiO 2 can photocatalyze the splitting of water, intense interest has been shown on photocatalytic H 2 O cleavage using TiO 2 . The TiO 2 surface is decisive for its catalytic performance because the critical processes (substrate adsorption, interfacial charge transfer, and redox reaction) readily take place on the surface. Exposure of diversified facets may result in dramatic discrepancies of the surface structures and therefore the performances. For instance, the theoretical calculations have revealed that water molecules can be dissociatively adsorbed on the anatase (001) facet via hydrogen bonding but molecularly on the (101) facet by Ti–O coordination. , In addition to substrate adsorption, several studies have unraveled the facet dependence of charge carrier behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery that TiO 2 can photocatalyze the splitting of water, intense interest has been shown on photocatalytic H 2 O cleavage using TiO 2 . The TiO 2 surface is decisive for its catalytic performance because the critical processes (substrate adsorption, interfacial charge transfer, and redox reaction) readily take place on the surface. Exposure of diversified facets may result in dramatic discrepancies of the surface structures and therefore the performances. For instance, the theoretical calculations have revealed that water molecules can be dissociatively adsorbed on the anatase (001) facet via hydrogen bonding but molecularly on the (101) facet by Ti–O coordination. , In addition to substrate adsorption, several studies have unraveled the facet dependence of charge carrier behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Scheme 1 shows the possible reaction mechanism of photocatalytic direct dehydrogenation of methanol to methyl formate. At the beginning of the reaction, methanol molecules react with the surface hydroxyls to give rise to methoxy groups and water (steps 1a and b in Scheme 1), [16][17][18]40 but the hydroxyls cannot be recovered after the methoxy groups are consumed during the reaction due to oxygen not being involved. Other studies showed that molecular methanol adsorbed on Ti 4+ is isoenergetic with its dissociated state (CH 3 O + H), suggesting that the exposed Ti 4+ sites on titania, resulting from the consumption of the surface methoxy groups, are prone to adsorbing methanol molecules to give rise to methoxy groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, TiO 2 has a band gap as large as 3.2 eV and hence is photocatalytically active only under UV light, which accounts for merely approximately 5% of solar radiation energy. Therefore, TiO 2 as a photocatalyst has a low utilization of solar radiation energy and insignificant photocatalytic performance [11][12][13]. However, combining TiO 2 with other narrow-band-gap semiconductor materials to construct heterojunctions can effectively enhance the photocatalytic performance of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%